Opioid-Sparing Analgesic Effects from Interscalene Block Impact Anesthetic Management During Shoulder Arthroscopy: A Retrospective Observational Study - Wu EB; Hsiao CC; Hung KC; Hung CT; Chen CC; Wu SC; Chin JC; Chen IW; Luo SD (Journal of Pain Research, 2023)
En-Bo Wu,1,* Chia-Chi Hsiao,2,* Kuo-Chuan Hung,3 Chao-Ting Hung,1 Chih-Chun Chen,1 Shao-Chun Wu,1 Jo-Chi Chin,4 I-Wen Chen,3 Sheng-Dean Luo5 1Department of Anesthesiology, Kaohsiung Chang Gung Memorial Hospital and Chang Gung University College of Medicine, Kaohsiung, Taiwan; 2Department of Family Medicine, Kaohsiung Veterans General Hospital, Kaohsiung, Taiwan; 3Department of Anesthesiology, Chi Mei Medical Center, Tainan, Taiwan; 4Department of Anesthesiology, Park One International Hospital, Kaohsiung, Taiwan; 5Division of Otolaryngology, Kaohsiung Chang Gung Memorial Hospital and Graduate Institute of Clinical Medical Science, College of Medicine, Chang Gung University, Kaohsiung, Taiwan*These authors contributed equally to this workCorrespondence: Sheng-Dean Luo, No. 123, Ta-Pei Road, Niao-Song District, Kaohsiung City, 833, Taiwan, Tel +886-7-7317123 (ext. 2788), Email rsd0323@cgmh.org.tw I-Wen Chen, No. 901, Zhonghua Road, Yongkang District, Tainan City, 710, Taiwan, Tel +886-6-2812811, Email mavising@gmail.comPurpose: Ultrasound-guided interscalene nerve block (UISB) is commonly used to alleviate postoperative pain during shoulder arthroscopy. This retrospective observational study aimed to evaluate the intraoperative advantages and analgesic effects of preoperative UISB.Patients and Methods: In this retrospective observational study, a total of 170 patients underwent shoulder arthroscopy at a tertiary medical center in southern Taiwan throughout 2019. After applying the exclusion criteria, 142 of these cases were included, with 74 and 68 in the UISB group and control groups, respectively. The primary outcome was the evaluation of intraoperative morphine milligram equivalent (MME) consumption. Secondary outcomes were sevoflurane consumption, the use of intraoperative antihypertensive drugs, and postoperative visual analog scale (VAS) scores in the post-anesthesia care unit (PACU) and in the ward at 24 h after surgery.Results: Preoperative UISB effectively reduced opioids and volatile gases during surgery, supported by a 48.1% and 14.8% reduction in the median intraoperative MME and sevoflurane concentrations, respectively, and showed less need for antihypertensive drugs. The preoperative UISB group also showed significantly better performance on the VAS in both the PACU and ward.Conclusion: Taken together, the preoperative UISB reduced not only intraoperative MME and sevoflurane consumption but also had satisfactory VAS scores in both the PACU and ward without any symptomatic respiratory complications. In summary, preoperative UISB is a reliable adjuvant analgesic technique and a key factor in achieving opioid-sparing and sevoflurane-sparing anesthesia and multimodal analgesia during shoulder arthroscopy.Graphical Abstract: Keywords: interscalene block, multimodal analgesia, opioid-sparing anesthesia, shoulder arthroscopy, volatile-sparing anesthesia